Sweet’s syndrome in pregnancy: a rare case report - Rawtani, Harshal A.; Chandrashekhar, Mubhachini; Phulpaghar, Aditi; Mathur, Ankita (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2022)
Sweet’s syndrome (SS) is a steroid-responsive dermatological condition characterized by fever, neutrophilia and a classical tender erythematous skin rash. Pregnancy-associated SS is an extremely rare clinical entity and must be kept in mind while approaching a case of skin rash in pregnancy. We reported a rare case of SS in pregnancy with classical features and characteristic histopathological features of neutrophilic dermatosis that had a benign course, resolving with topical steroid treatment instead of the usual systemic steroids.